Models of Individual Verbal Assertive Behavior - Adamchuk, Iryna (East European Journal of Psycholinguistics, 2015)
The problem of individual assertiveness is increasingly attracting attention of scientists, because this personal quality allows defining human limits to form one’s confidence, responsibility, and preserve freedom. The importance of this personality feature for his/her functioning in human society, on the one hand, and insufficient development of this category in psychological literature on the other, determines the relevance of research. The results of theoretical analysis of personal assertiveness psychological manifestation, in particular, through verbal means, are presented in the article. Operationalization of the theoretical concept of individual assertiveness and its conceptual limits are determined. Models of verbal assertive behavior in problem situations are pointed out, five stages of its implementation are singled out and its key characteristics are identified. References Andriyenko, E. (2000). Sotsialnaya Psyhologiya [Social Psychology]. Moscow: Academia. Basenko, V., Zhukov, B., Romanov, A. (2012). Orhanizatsionnoye Povedeniye [Organizational Behavior]. Moscow: Dashkov i Co. Bishop, S. (2001). Trening Assertivnosti [Assertiveness Training]. S.-Petersburg: Piter. Fedorov, A. (2002). Kohnitivno-Povedencheskaia Psihoterapiia [Cognitive-Behavioral Psychotherapy]. S.-Petersburg: Piter. Filonenko, M. (2008). Psyholohiia Spilkuvannia. [Psychology of Communication]. Kyiv: Tsentr Uchbovoii Literatury. Hall, C.S., Lindsey, G. (2002). Theories of Personality. N.Y.: John Wiley and Sons, 1970. Kapponi, V., Novak, T. (1995). Kak Delat’ Vse Po-svoemu, ili Assertivnost’ – v Zhyzn’ [How to Do Whatever I want or Assertiveness in Life]. S.-Petersburg: Piter. Kashapov, M. (2003). Teoriia i Praktika Resheniia Konfliktnyh Situatsyi [Theory and practice of Conflict Resolution]. Moscow: Remder. Keenan, K. (1996). The Management Guide to Communicating. N.Y: Ravette Pub Ltd. Stepanov, S. (2012). Mify i Tupiki Pop-psiholohii [Myths and Deadlocks of Pop Psychology]. Moscow: Eksmo. Verderber, R. Verderber, K. (2003). Psyholohiia Obshcheniia [Psychology of communication]. S.-Petersburg: Praim-Evroznak.